2022
DOI: 10.3389/fphar.2022.862125
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Small-Molecule Antagonist Combats Chemoresistance and Enhances Immunotherapy in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer as the absence of cell surface receptors renders it more difficult to be therapeutically targeted. Chemokine receptor 2 (CXCR2) has been suggested not only to promote therapy resistance and suppress immunotherapy but it also to possess a positive cross-talk with the multifunctional cytokine transforming growth factor beta (TGF-β). Here, we showed that CXCR2 and TGF-β signaling were both upregulated in human TNBC biopsies. CXCR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Targeting neutrophils is challenging owing to the lack of tractable targets; however, inhibition of C–X–C chemokine receptor 2 (CXCR2) and its ligand, C–X–C chemokine ligand 8 (CXCL8, also known as IL-8), has been used to prevent neutrophil recruitment to tissues 17 . A recent study suggested that the CXCR2 inhibitor, AZD5069, is a promising approach to improve triple-negative breast cancer treatment because the blockade of CXCR2 significantly reduces the infiltration of neutrophils and improves the efficacy of immune checkpoint blockade in in vitro tests 18 . Tumor cells also induce neutrophil extrusion of NETs by secreting CXCR2 ligands 4 .…”
Section: Neutrophil-dependent Therapiesmentioning
confidence: 99%
“…Targeting neutrophils is challenging owing to the lack of tractable targets; however, inhibition of C–X–C chemokine receptor 2 (CXCR2) and its ligand, C–X–C chemokine ligand 8 (CXCL8, also known as IL-8), has been used to prevent neutrophil recruitment to tissues 17 . A recent study suggested that the CXCR2 inhibitor, AZD5069, is a promising approach to improve triple-negative breast cancer treatment because the blockade of CXCR2 significantly reduces the infiltration of neutrophils and improves the efficacy of immune checkpoint blockade in in vitro tests 18 . Tumor cells also induce neutrophil extrusion of NETs by secreting CXCR2 ligands 4 .…”
Section: Neutrophil-dependent Therapiesmentioning
confidence: 99%
“…However, it was not associated with the improved clinical outcomes explored in the trial, so additional clinical trials are needed to explore its effectiveness ( O'Byrne et al, 2016 ; De Soyza et al, 2015 ). AZD5069 has been shown to improve TGF-β signaling pathway-mediated adriamycin resistance through inhibition of CXCR2 in triple-negative breast cancer cells and to enhance atezolizumab immunotherapy efficacy ( Ghallab et al, 2022 ). Therefore, the results of the ongoing clinical trials of AZD5069 antitumor therapy are worthy of our expectation.…”
Section: Intracellular Signaling Pathways Of Cxcl7mentioning
confidence: 99%
“…They can also polarize neutrophils to a pro-tumorigenic phenotype [ 26 , 226 ]. CXCR2 upregulation was found in TNBC themselves and was suggested as a novel cancer stem-like cell marker for TNBC [ 272 , 273 ]. Ghallab et al showed that CXCR2 inhibition with the small-molecule inhibitor AZD5069 in TNBC culture eliminated doxorubicin resistance and improved the efficacy of atezolizumab, a monoclonal antibody against PD-L1 [ 273 ].…”
Section: Neutrophil In Cancer Therapy: Potential Strategiesmentioning
confidence: 99%
“…CXCR2 upregulation was found in TNBC themselves and was suggested as a novel cancer stem-like cell marker for TNBC [ 272 , 273 ]. Ghallab et al showed that CXCR2 inhibition with the small-molecule inhibitor AZD5069 in TNBC culture eliminated doxorubicin resistance and improved the efficacy of atezolizumab, a monoclonal antibody against PD-L1 [ 273 ]. In the HCC with non-alcoholic steatohepatitis (NASH-HCC) mouse model resistant to anti-PD-1, AZD5069/anti-PD-1 combination therapy suppressed the tumor burden and extended survival [ 274 ].…”
Section: Neutrophil In Cancer Therapy: Potential Strategiesmentioning
confidence: 99%